1)  [latex] \frac{x + 2}{ x^{2} - 2x + 1} * \frac{3(x - 1)}{ x^{2} - 4} - \frac{3}{x - 2} ;[/latex]

 1)  [latex] \frac{x + 2}{ x^{2} - 2x + 1} * \frac{3(x - 1)}{ x^{2} - 4} - \frac{3}{x - 2} ;[/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{x+2}{(x-1) ^{2} } * \frac{3(x-1)}{(x-2)(x+2)} = \frac{3}{(x-1)(x-2)} [/latex] [latex]\frac{3}{(x-1)(x-2)} - \frac{3}{x-2} = \frac{3-3x+3}{(x-1)(x-2)} = \frac{3(2-x)}{(x-1)(x-2)} = \frac{3}{1+x} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы